Ag-Doped MoSe2/ZnO Heterojunctions: A Highly Responsive Gas-Sensitive Material for Selective Detection of NO Based on DFT Study - Tao He; Hongcheng Liu; Jing Zhang; Yuepeng Yang; Yuxiao Jiang; Ying Zhang; Jiaqi Feng; Kelin Hu (Nanomaterials, 2023)
In this work, the adsorption and sensing behavior of Ag-doped MoSe2/ZnO heterojunctions for H2, CH4, CO2, NO, CO, and C2H4 have been studied based on density functional theory (DFT). In gas adsorption analysis, the adsorption energy, adsorption distance, transfer charge, total electron density, density of states (DOS), energy band structure, frontier molecular orbital, and work function (WF) of each gas has been calculated. Furthermore, the reusability and stability of the Ag-doped MoSe2/ZnO heterojunctions have also been studied. The results showed that Ag-doped MoSe2/ZnO heterojunctions have great potential to be a candidate of highly selective and responsive gas sensors for NO detection with excellent reusability and stability.